Relations of Philosophy, Religion, and Science - Muh Bukhari (Scientia Integritas Utama, 2022)
Philosophy, religion and science have always been united in human civilization and humanity. But, the relationship can go up and down or even try to dominate one another. Human civilization which basically cannot be separated from philosophy, religion, and science raises philosophical questions in this study, namely how are the relations of philosophy, religion, and science in humans and humanity's lives. Basically, there is a relationship between philosophy, religion and science throughout human civilization. It can be seen in the history of mankind that it has always been seeking God. The similarity between science, philosophy and religion is to find the truth. Science through its scientific method tries to find the truth, philosophy in its own way discovers the essence of things both about nature, humans and about God. Meanwhile, religion, with its own characteristics, provides answers to all basic questions regarding nature, humans and God.